Locating the Site of Neuropathic Pain In Vivo Using MMP-12-Targeted Magnetic Nanoparticles. (6th March 2019) - Husain, Syeda Fabeha; Lam, Raymond W. M.; Hu, Tao; Ng, Michael W. F.; Liau, Z. Q. G.; Nagata, Keiji; Khanna, Sanjay; Lam, Yulin; Bhakoo, Kishore; Ho, Roger C. M.; Wong, Hee-Kit
Abstract : Neuropathic pain remains underrecognised and ineffectively treated in chronic pain sufferers. Consequently, their quality of life is considerably reduced, and substantial healthcare costs are incurred. The anatomical location of pain must be identified for definitive diagnosis, but current neuropsychological tools cannot do so. Matrix metalloproteinases (MMP) are thought to maintain peripheral neuroinflammation, and MMP-12 is elevated particularly in such pathological conditions. Magnetic resonance imaging (MRI) of the peripheral nervous system has made headway, owing to its high-contrast resolution and multiplanar features. We sought to improve MRI specificity of neural lesions, by constructing an MMP-12-targeted magnetic iron oxide nanoparticle (IONP). Its in vivo efficiency was evaluated in a rodent model of neuropathic pain, where the left lumbar 5 (L5) spinal nerve was tightly ligated. Spinal nerve ligation (SNL) successfully induced mechanical allodynia, and thermal hyperalgesia, in the left hind paw throughout the study duration. These neuropathy characteristics were absent in animals that underwent sham surgery. MMP-12 upregulation with concomitant macrophage infiltration, demyelination, and elastin fibre loss was observed at the site of ligation. This was not observed in spinal nerves contralateral and ipsilateral to the ligated spinal nerve or uninjured left L5 spinal nerves. The synthesised MMP-12-targeted magnetic IONP was stable and nontoxic in vitro . It was administered onto the left L5 spinal nerve by intrathecal injection, and decreased magnetic resonance (MR) signal was observed at the site of ligation. Histology analysis confirmed the presence of iron in ligated spinal nerves, whereas iron was not detected in uninjured left L5 spinal nerves. Therefore, MMP-12 is a potential biomarker of neuropathic pain. Its detection in vivo, using IONP-enhanced MRI, may be further developed as a tool for neuropathic pain diagnosis and management.